Division of labour promotes the spread of information in colony emigrations by the ant Temnothorax rugatulus. Issue 1924 (8th April 2020) - Valentini, Gabriele; Masuda, Naoki; Shaffer, Zachary; Hanson, Jake R.; Sasaki, Takao; Walker, Sara Imari; Pavlic, Theodore P.; Pratt, Stephen C.
Abstract : The fitness of group-living animals often depends on how well members share information needed for collective decision-making. Theoretical studies have shown that collective choices can emerge in a homogeneous group of individuals following identical rules, but real animals show much evidence for heterogeneity in the degree and nature of their contribution to group decisions. In social insects, for example, the transmission and processing of information is influenced by a well-organized division of labour. Studies that accurately quantify how this behavioural heterogeneity affects the spread of information among group members are still lacking. In this paper, we look at nest choices during colony emigrations of the ant Temnothorax rugatulus and quantify the degree of behavioural heterogeneity of workers. Using clustering methods and network analysis, we identify and characterize four behavioural castes of workers—primary, secondary, passive and wandering—covering distinct roles in the spread of information during an emigration. This detailed characterization of the contribution of each worker can improve models of collective decision-making in this species and promises a deeper understanding of behavioural variation at the colony level.